Atomic Layer Deposition of ZnO on CuO Enables Selective and Efficient Electroreduction of Carbon Dioxide to Liquid Fuels. (10th September 2019) - Ren, Dan; Gao, Jing; Pan, Linfeng; Wang, Zaiwei; Luo, Jingshan; Zakeeruddin, Shaik M.; Hagfeldt, Anders; Grätzel, Michael
Abstract: Electrochemical reduction of carbon dioxide, if powered by renewable electricity, could serve as a sustainable technology for carbon recycling and energy storage. Among all the products, ethanol is an attractive liquid fuel. However, the maximum faradaic efficiency of ethanol is only ≈10 % on polycrystalline Cu. Here, CuZn bimetallic catalysts were synthesized by in situ electrochemical reduction of ZnO‐shell/CuO‐core bi‐metal‐oxide. Dynamic evolution of catalyst was revealed by STEM‐EDS mapping, showing the migration of Zn atom and blending between Cu and Zn. CuZn bimetallic catalysts showed preference towards ethanol formation, with the ratio of ethanol/ethylene increasing over five times regardless of applied potential. We achieved 41 % faradaic efficiency for C2+ liquids with this catalyst. Transitioning from H‐cell to an electrochemical flow cell, we achieved 48.6 % faradaic efficiency and −97 mA cm −2 partial current density for C2+ liquids at only −0.68 V versus reversible hydrogen electrode in 1 m KOH. Operando Raman spectroscopy showed that CO binding on Cu sites was modified by Zn. Free CO and adsorbed *CH3 are believed to combine and form *COCH3 intermediate, which is exclusively reduced to ethanol. Abstract : Bimetallische Katalyse : Durch Atomlagenabscheidung von ZnO auf CuO werden in situ reduzierte CuZn‐Nanodrähte erzeugt, die als selektive Katalysatoren für die Elektroreduktion von CO2 zu Ethanol wirken. Es wird postuliert, dass die Zn‐katalysierte, überschüssige CO‐Bildung und die schnelle Kinetik der *CH3 ‐Bildung bei hohem Überpotential auf Cu die entscheidenden Faktoren für die Ethanol‐Selektivität sind.